Compression test of built-up C section cold-formed steel with openings - Mohamad Nabil, Mohamed (2019)
This paper aims to determine the ultimate load of built-up C section cold-formed steel with openings compared to single C section and study the buckling behavior of built-up C section. Cold-formed steels are widely used in construction industry, manufacturing technologies and relevant standards. Cold-formed steels are widely available with difference sizes and shapes. Cold-formed steel sections are manufactured with difference process such as cold roll forming and press brake operation. In the tests, compression loading were imposed on fix ended short columns with opening series. There are total of 8 specimens was conducted as to get an accurate result to show the behavior and strength of built-up cold-formed steel. The built-up column consists of two individual cold-formed steel lipped channels placed back-to-back and connected at the web using two self-drilling screw fasteners at specified spacing along the column length. Both end of each columns will be welded with a steel plate to act as fixed support. This paper presents a detailed descriptions of an experimental and theoretical studies to investigate the maximum load and buckling behavior of cold-formed steel columns. Mode of failure split into four categories such as local buckling, distortional buckling, warping and flexural buckling. All of specimen in openings give different data. Specimen without opening give more higher maximum load compare to specimen with opening. The use of transducer in the compression test gives the earlier sign how column structures behave under axial load.